The theory of literature as a declaration of love - Mihet, Marius (Swedish Journal of Romanian Studies, 2019)
In Frumoasa necunoscută. Literatura și paradoxurile teoriei, Carmen Mușat analyzes and systemizes the relational character of literature and the discourses on literature. She revisits famous notions of modernity which can be capitalized on in our current context, where we speak of the death of the author and even the end of literary theory. In all of the approaches that she takes in the book, the author is certain that the theorist and his presence in the world retain a valid purpose, as they can counterargue, wherever the case may be, and justify the beauty of literature from novel points of view. Frumoasa necunoscută presents to us an inventory for an ideal way to look upon the world and literature. Carmen Mușat is a researcher who is up to date with the most sophisticated conceptual systems. The result of this is a narration under the form of a complex declaration of love for literature and the paradoxes of theory.